Searching differences in patients with heart failure with clinical suspicion of cardiac amyloidosis: the REGAMIC study design - Prado Salamanca-Bautista; RocÃo Ruiz-Hueso; Miguel A. Rico-Corral; JesÃºs Casado-Cerrada; Sergi Yun-Viladomat; Ãlvaro GonzÃ¡lez-Franco; Alicia Conde-Martel; Pau LlÃ cer-Iborra; JosÃ© C. ArÃ©valo-Lorido; MarÃa A. Quesada SimÃ³n; Marta SÃ¡nchez-Marteles; Eduardo Carmona-Nimo; et al. (Spanish Journal of Medicine, 2023)
Introduction and objectives: Cardiac amyloidosis (CA) is not a rare cause of heart failure (HF). In Spain, more than 60% of HF patients admitted to hospitals are treated in Internal Medicine Services. REGAMIC is a registry designed by the HF Working Group of the Spanish Society of Internal Medicine to improve the suspicion criteria and the selection of patients in whom CA must be ruled out. The main objective is to evaluate the differential characteristics between two groups of HF patients with suspicion of CA: confirmed vs ruled out cases. The secondary objectives are to evaluate the data on which investigators have based the suspicion of CA, and to identify prognostic differences between both groups. Methods: A multicenter, observational, prospective, cohort study of at least 600 patients, with a 2-year follow-up. Inclusion criteria: patients of Internal Medicine Services, aged ≥ 18 years, with HF and left ventricular hypertrophy (septum or posterior wall ≥ 12 mm), with suspicion of CA. Clinical, electrocardiographic, echocardiographic, and follow-up data will be compared between both groups of patients. Results and discussion: If the recommendations of the 2021 European Society of Cardiology Consensus on CA are followed, a large number of patients should be studied to rule out CA. REGAMIC can improve the selection of patients in whom CA will be ruled out and make the study more cost-effective. Conclusions: Our registry aims to improve the knowledge about differential characteristics between HF patients with clinical suspicion of CA and may increase knowledge of the natural history of the disease.